PERLINDUNGAN HUKUM TERHADAP PRIVASI DATA PRIBADI DI ERA DIGITAL - Sadillah Ahmad, Ridho; Puspaningtyas, Dyah Ayu; Ismariy, Muhammad Nur Karim Al (The Juris, 2025)
In an increasingly fast-paced and connected digital era, the protection of personal data privacy has become a very urgent and complex issue. Information and communication technologies have facilitated the widespread collection, storage and distribution of personal data, presenting new challenges to the protection of privacy rights, particularly in Indonesia. This phenomenon is exacerbated by various cases of data leakage and misuse of personal information that emphasize the importance of a strong and effective legal framework to protect individual privacy. This study aims to evaluate the effectiveness of existing regulations, such as Article 26 of the ITE Law and PP PSTE, in protecting personal data privacy in Indonesia, and to examine the draft personal data protection law (RUU PDP) which is expected to provide more comprehensive protection. The research method used is a normative juridical approach, with literature study as the main tool for collecting data. The results show that although the existing regulations already provide an important legal foundation, there are still weaknesses in implementation and law enforcement. Lack of public awareness about privacy rights, as well as weak law enforcement against data privacy violations, are the main obstacles in the protection of personal data privacy. The conclusion of this study is that improvements in regulation, stricter law enforcement, and better education to the public are needed to improve the protection of personal data privacy. The PDP Bill is expected to address some of these weaknesses by providing a clearer and more comprehensive legal framework.